Chinese social credit system as the tool of governance in the digital era - Golubev, Sergey G.; Suhak, Vadzim K. (Journal of the Belarusian State University. Sociology, 2020)
The article illustrates the issues of the formation of social credit system in the People’s Republic of China. Key principles of creating and functioning of the system are discussed. Study makes separate analysis of the use of the system for scoring of citizens and organizations, including public and private sector. Authors focus on the differences in the perception of the social credit system from the points of view of Western and Chinese citizens.